(3JYHjQ GdQDjGs - (3eMeO Hf SjQjfs
(3ChdgG (B:s
(3CeG HYO bGd eMeO Hf SjQjf QMeg Gddg JYGdi (B" (3GdPjf BefhG hcGfhG jfabhf dge GdHTQi ai GdMjGI GdOfjG hai GdBNQI s
(3BNQgG (B:s
(3hCNQS Yfi CdSfJge hca Yfi LhGQMge hCTZdge Yfi HeG TFJ Efc Ydi cd TF bOjQ hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg CLeYjf s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1405s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3JYHjQ GdQDjGs